“Imaginaries about the desert through the genealogy of ideas” - Carmona Ochoa, Gabriela (UNIVERSIDAD DE SONORA, 2022)
This article explores the construction of imaginaries through the idea that they are formed through frames of inherited ideas. The vision of the desert in the New World from one of its conquerors, Captain Alberto del Canto, is explored. Searching around the formation of the collective components of his imaginary through the analysis of his genealogical lines, a way is found to form for us a coherent image of the contents of his imaginary, to understand the actions that led him to undertake the foundations in the arid northeast of Mexico. This means of inquiry has been tested through the analysis of genealogies of objects, when studies have been carried out on the morphogenesis of “lineages of objects”, but it will be the first time that it is undertaken seeking to penetrate research on social imaginaries focusing on the vision of the historical characters who undertook the conquest and colonization of territories beyond what was known until then.